Analisis Kontekstual BMT Al-Istiqomah Maleber Ciamis: Pengaruh Peningkatan Pendapatan BMT Melalui Pembiayaan Mudharabah Dan Musyarakah - Lutpi Alpauzi; Nila Nurochani; Mulia Amirullah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Objectives and targets that can be achieved for each study. There are objectives to be achieved, including: To determine the effect of mudharabah financing to boost BMT Al-Istiqomah Maleber Ciamis income, To determine the effect of musyarakah financing on increasing BMT Al-Istiqomah Maleber Ciamis income, and to determine the effect of Mudharabah and musyarakah financing on increasing income of BMT Al-Istiqamah Maleber Ciamis. The scientific approach to obtaining data for a specific purpose is the research method. Quantitative statistical methods are used in this study. The results of this study This study shows that (1) revenue growth is significantly and positively affected by Mudharabah financing. It can even be said that the higher the mudharab support, the higher the compensation for BMT Al-Istiqamah Maleber Ciamis. (2) The consequences of the review show that the musyarakah monetary variable influences salary development. As a result, musyarakah funds can be said to increase the income of BMT Al-Istiqamah Maleber Ciamis. (3) Mudharabah and musyaraq financing simultaneously have a significant positive impact on income.